2020
DOI: 10.1001/jamasurg.2019.5083
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care and End-of-Life Outcomes Following High-risk Surgery

Abstract: IMPORTANCE Palliative care has the potential to improve care for patients and families undergoing high-risk surgery.OBJECTIVE To characterize the use of perioperative palliative care and its association with family-reported end-of-life experiences of patients who died within 90 days of a high-risk surgical operation. DESIGN, SETTING, AND PARTICIPANTSThis secondary analysis of administrative data from a retrospective cross-sectional patient cohort was conducted in the Department of Veterans Affairs (VA) Healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 47 publications
(95 reference statements)
2
49
0
2
Order By: Relevance
“…Palliative consultation is associated with an overall improvement in EOL care, communication, and support, according to families of deceased patients. 14 It has also been shown to enhance patients' quality of life and mood, improve documentation of resuscitation preferences, and lead to less aggressive care at the EOL, including less chemotherapy. 15 Integration of palliative care in the care of patients hospitalized with acute heart failure has been associated with improved quality of life, decreased symptom burden and depressive symptoms, and increased participation in advance care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative consultation is associated with an overall improvement in EOL care, communication, and support, according to families of deceased patients. 14 It has also been shown to enhance patients' quality of life and mood, improve documentation of resuscitation preferences, and lead to less aggressive care at the EOL, including less chemotherapy. 15 Integration of palliative care in the care of patients hospitalized with acute heart failure has been associated with improved quality of life, decreased symptom burden and depressive symptoms, and increased participation in advance care planning.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Veterans Affairs study evaluating 95,204 patients who underwent high-risk surgery, only 770 (0.8%) received a palliative care consultation before surgery. 62 Of all the patients who died within 90 days, 29.9% had received a palliative care consultation, and 5.6% received consultation before surgery. Families of these patients reported an overall significant increase in satisfaction with end-of-life care, communication, and support.…”
Section: Patient-centered Decisionsmentioning
confidence: 99%
“…Studies are underway to evaluate routine inclusion of specialist PC for cancer patients undergoing non-palliative oncologic surgery (98). Prior research within the Veterans Affairs (VA) medical system has shown that the survivors of high-risk surgical procedures who died and received an inpatient PC consultation were more likely to rate their loved ones' overall care, EOL communication and support as excellent when compared to families of decedents who did not receive PC (99). A corollary study within the VA system demonstrated that surgical patients were less likely to receive a PC consult than medical patients, despite the fact that 22% of the patients had at least one major surgical procedure in their final year of life (100).…”
Section: An Unmet Needmentioning
confidence: 99%